(untitled) (Proceedings of the International Conference on Public Health, 2022)
HIV/AIDS cases in Bali surge up to 700 in general population according to health department data. Sekeha teruna, a local Bali’s youth organization in every hamlet could potentially further optimize its role based on the concern of the Bali’s young generation. This study aims to present stimulation of Bali young generation awareness level to role of Sekeha teruna to fend off the spreading of HIV/AIDS in the community as health collaborative approach based on local genius. We obtained data through questionnaire survey by non-probability sampling technique to 200 young people spread across 4 districts in Denpasar City (North, East, South, West) to find the awareness level percentage; and in-depth interview with some experts at Komisi Penanggulangan AIDS (KPA) and Kita Sayang Remaja (KISARA), Bali Province about two weeks. Based on the results of the analysis of research data through a questionnaire survey to people age  18 years old, it was found that the dominance of awareness level is quite high (35.9%) and high (26.1%). Therefore, it could be the basic foundation of stimulation for the role of sekeha teruna, especially as spiritual motivators, persuasive and pervasive agent, personality-forming factors and supervisory functions in behavior namely Awareness, Interest, Evaluation, Trial, Adoption (AIETA). Since the high level of awareness, stimulation of Bali’s youth generation to sekeha teruna possess a bright long-term prospect in creating a conducive climate in HIV/AIDS spreading in communities as a public health collaborative approach. However, there are still obstacles such as the existence of different social ties, the influence of social media distortion, and there are still young people not joining the sekeha teruna.